ANALYSIS OF THE EFFECTIVENESS OF STEM-BASED PjBL MODEL TO DEVELOP STUDENTS' CREATIVITY - Carsono, Adi; Heliawati, Leny; Permana, Irvan (Universitas Pakuan, 2025)
This study aims to analyze the effectiveness of the STEM-based Project-Based Learning (PjBL) model in improving students' scientific creativity on the topic